A modified spectral-velocity-based earthquake intensity measure for super high-rise buildings. Issue 162 (November 2022) - Lai, Xiao; He, Zheng; Chen, Yuanyuan; Zhang, Yantai; Li, Zhenhui; Guo, Zhuang; Ma, Ling
Abstract: To provide an efficient and stable connection between seismic hazards and structural demands of super high-rise buildings, a modified spectral-velocity-based intensity measure (IM) is proposed in a general manner with the combination coefficients and the optimal number of modes estimated through the non-uniform flexural-shear coupled model (FSM-MS). With numerous FSM-MSs generated from statistical ranges of vibration periods, the optimal number of modes is regressed for near-field and far-field ground motions, respectively. Utilizing seven structural models with different heights and dynamic properties, the performance of selected IMs is systematically studied in two stages. The superiority of the proposed IM in stable and high efficiency is obviously observed through seven FSM-MSs, together with the other 19 IMs. Its sufficiency and scaling robustness are fully demonstrated by two significantly distinct super high-rise buildings. The proposed IM is promising as a specialized and desirable tool in the seismic performance evaluation of super high-rise buildings. Highlights: A spectral-velocity-based intensity measure (IM) with the adaptive combination coefficients and modal number is proposed. The physical background of spectral velocity as the core of the IM for super high-rise buildings is systematically justified. A two-stage strategy for evaluating IMs' performance is proposed based on simplified and refined structural models. The superior stability and efficiency of the proposed IM are fully demonstrated by the comparison with the other 19 IMs.